Q. 53.7( 9 Votes )

If 5t - 3 = 3t - 5, then t = ?
A. 1

B. - 1

C. 2

D. – 2

Answer :

5t - 3 = 3t - 5   .... (1)


By transposition of -3 on RHS we get,
 5t  = 3t - 5 + 3
5t = 3t - 2
By transposition of 3t on LHS we get,
5t - 3t = - 2

⇒ 2t = - 2

⇒ t = - 1
Check:

Put the value of t in (1),
LHS
5(-1) - 3 = -5 -3 
            = -8
RHS
3t - 5 = 3(-1) - 5
         = -3 - 5
        = -8
As LHS =RHS
The value t=-1 is correct.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.